2018
DOI: 10.1101/414193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factor cooperation for chromosome discrimination in Drosophila

Abstract: Transcription regulators select their genomic binding sites from a large pool of similar, non-functional sequences. Although general principles that allow such discrimination are known, the complexity of DNA elements often precludes a prediction of functional sites.The process of dosage compensation in Drosophila allows exploring the rules underlying binding site selectivity. The male-specific-lethal (MSL) Dosage Compensation Complex selectively binds to some 300 X-chromosomal 'High Affinity Sites' (HAS) conta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 73 publications
3
27
0
Order By: Relevance
“…3c). Importantly, the observed difference in APs binding at the B2 boundary genomic region in Kc167 cells is not due to differential chromatin accessibility since Kc167 and S2 cells show a remarkable similar ATAC-seq profile at the Notch locus 44 ( Supplementary Fig. 3b, c).…”
Section: Resultsmentioning
confidence: 87%
“…3c). Importantly, the observed difference in APs binding at the B2 boundary genomic region in Kc167 cells is not due to differential chromatin accessibility since Kc167 and S2 cells show a remarkable similar ATAC-seq profile at the Notch locus 44 ( Supplementary Fig. 3b, c).…”
Section: Resultsmentioning
confidence: 87%
“…To characterize the direct DNA binding of MSL2, DNA fragments from paired‐end sequencing runs were computationally subset to sizes between 10 and 130 bp, i.e., sub‐nucleosomal length, since it has been previously shown that HAS are nucleosome‐free . For clarity, we refer to those binding events as direct “DNA” binding (Fig A).…”
Section: Resultsmentioning
confidence: 99%
“…αMSL1, αMSL2, αMSL3, αMOF, and αMLE antibodies were previously described in Refs . αSXL antibody was kindly provided by F. Gebauer and previously described in Ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the MSL2 component of MSLc has a low affinity for MREs, MSL complex requires synergy with an essential, non sex-specific, zinc finger adapter protein known as chromatinlinked adapter for MSL proteins (CLAMP) in order to stabilize its binding to MREs [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%